Estudio de prefactibilidad para la fabricación y comercialización de cerveza artesanal a base de la cascarilla del cacao (2021)
The purpose of this research is to demonstrate the manufacturing and commercialization process of a new potential product mainly aimed at the Bogotá market. This can be achieved with the initial installation of a microbrewery company that will try to get the best out of a characteristic fruit of Colombia such as cocoa, with the reuse of its residue such as the cocoa husk. In most cases the processing plants of is fruit discard that vital raw material for the project, in the pulping stage, though it can create added value for farmers in the regions. We proceed to identify all the stages of the beer production process, establishing the optimal quantities and extracting that taste of cocoa that is desired by many people. For the operation of the plant, all the minimum standards and legal requirements that will govern the company are evaluated as well as the registration of the company name and possible innovative designs in its presentation that will differentiate it from the other beers on the market. In relation to the commercialization, there are several factors that may affect the investigation. In this initial case there will be no intermediaries, so all the distribution logistics will be done by the same company in the same way. The demand for craft beer in Bogota was found to be unsatisfied. (Dinero, 2019)